Understanding myasthenia gravis and advances in its management - Kaminski, Henry J. (Henry Stewart Talks, 2023)
Clinical presentation of myasthenia gravis, Diagnosis of myasthenia gravis, Pathophysiology of myasthenia gravis, Standard and emerging therapies, Clinical trials on the treatment of myasthenia gravis